Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content 1. The strategic Israel stages to Separation of South Sudan from the Republic of Sudan Mr. Ibrahim Youssef Hammad Odeh 2. The role of cybersecurity in reducing the number of cybercrimes In Aqaba Governorate "Using geographic information systems" Ms. Suzan Muhammad Saleh Al-Anouz 3. Rising centers in the Inawen low: Its emergence and role in the territorial organisation, Oud Amlil as a model Dr. Ali Neddama, Dr. Jaouad El-Bazoui, Mr. Samir El-Ouardi, Dr. Abdelouahed Bouberria 4. Civil/social approaches to the phenomenon of the alienation of the Gulf family Ms. Amira Mohammed Alajmi, Co-Prof. Abubaker Mohammed Ibrahim 5. The Professional Practice of the Social Worker’s Role between Reality and Challenges: A Descriptive Study on A Sample of Social Workers at Health Institutions in Yanbu - 2023 Mr. Suhayb Mousa Abu Shurayyan 6. Social solidarity through food in a society in the eastern Arabian Peninsula In the Abbasid era 247-656 AH / 861-1258 AD Ms. Asma Khaled Abdulla